KUESIONER PERILAKU BERISIKO PENGENDARA SEPEDA MOTOR: STUDI LITERATUR - Jefri, Nabila Dearmi (LPPM Universitas Bina Bangsa, 2024)
Traffic accidents are the 8th leading cause of death in the world based on WHO data in 2020. This figure is dominated by motorcyclists with a fatality percentage of road accidents of 75%. This happens because motorcycles do not have much protection if they are involved in an accident. This data shows that motorcyclists are in dangerous conditions. Given the danger of motorcycle accidents, this article aims to conduct a literature study related to questionnaires/instruments that can identify the factors that cause accidents and the severity of motorcycle accidents. Articles in the form of journals and proceedings in English published internationally were collected and obtained 119 articles. In-depth analysis was carried out on articles published in 2007 to early 2022, namely research from Elliott et al. (2007) in the United Kingdom, Putranto (2014) in Indonesia, Bui et al., (2020) in Vietnam, Uttra et al., (2020) in Thailand, and Andrijanto et al. (2022) in Indonesia. The main finding of the article states that the questionnaire is formed into indicators consisting of 5 factors (traffic errors, speed violations, stunts, safety equipment, and control errors). Common linear modeling methods show that age, experience, annual mileage are the main predictors of accident cause risk. The exploratory factor analysis (EFA) of the MRBQ revealed the indicators were grouped into four distinct factors from 36 question items. The addition of risky behavior factors for motorcyclists and the addition of local behavior factors are a solution effort to complete the questionnaire for assessing the behavior of motorcyclists related to the existence of typical risky behaviors in Indonesia. In this study, the validation of the questionnaire was only carried out on the islands of Java and Sumatra, because these two regions occupied the highest position in terms of the number of motorcycle accidents per year for the last five years (2016-2021)